2013
DOI: 10.1002/cne.23332
|View full text |Cite
|
Sign up to set email alerts
|

Glycine‐immunoreactive neurons in the brain of a shark (Scyliorhinus canicula L.)

Abstract: The glycinergic cell populations in the brain of the lesser spotted dogfish were studied by a glycine immunofluorescence method. Numerous glycine-immunoreactive (Gly-ir) neurons were observed in different brain nuclei. In the telencephalon, Gly-ir cells were observed in the olfactory bulb, telencephalic hemispheres, and preoptic region. In the hypothalamus, cerebrospinal fluid-contacting Gly-ir neurons were observed in the lateral and posterior recess nuclei. Coronet cells of the saccus vasculosus were Gly-ir.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 183 publications
(365 reference statements)
0
22
0
Order By: Relevance
“…The primary sensory projections of the glossopharyngeal and vagal nerves on this column have been studied experimentally in a ray (Barry, 1987). Immunohistochemical studies in a dogfish indicate that the vagal lobe contains neurochemically heterogeneous neuronal populations (Carrera et al, 2005(Carrera et al, , 2012Anad on et al, 2013), similar to teleost taste centers, but their projections have not been investigated. In non-teleost actinopterygian fishes, the SGN/V has been reported in sturgeon (Huesa, 2002;Graña et al, 2012) and gar (Grone and Maruska, 2015), and a similar nucleus was observed in cladistians (Graña et al, 2013).…”
Section: Comparison With Mammals and Other Vertebratesmentioning
confidence: 99%
“…The primary sensory projections of the glossopharyngeal and vagal nerves on this column have been studied experimentally in a ray (Barry, 1987). Immunohistochemical studies in a dogfish indicate that the vagal lobe contains neurochemically heterogeneous neuronal populations (Carrera et al, 2005(Carrera et al, , 2012Anad on et al, 2013), similar to teleost taste centers, but their projections have not been investigated. In non-teleost actinopterygian fishes, the SGN/V has been reported in sturgeon (Huesa, 2002;Graña et al, 2012) and gar (Grone and Maruska, 2015), and a similar nucleus was observed in cladistians (Graña et al, 2013).…”
Section: Comparison With Mammals and Other Vertebratesmentioning
confidence: 99%
“…As a further specificity control, the antiserum to BLBP was tested by western blotting with protein extracts from adult turbot brain. Protein extraction and blotting were performed by standard procedures (for details see Adrio, Rodríguez‐Moldes, & Anadón, ; Anadón, Rodríguez‐Moldes, & Adrio, ). In these blots, the BLBP antibody (Millipore, dilution 1:1,000) stained a single protein band of about 14–15 kDa (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…They appear to have a glial nature, as they express glial fibrillary acidic protein (GFAP) and vimentin (Arochena et al , ; Sueiro et al , ). Other evidence, however, has demonstrated that they contain glycine (Adrio et al , ; Anadón et al , ), a neuroactive substance classically associated to neurons. Coronet cells could be involved in sensory (Van de Kamer & Schuurmans, ) and secretory (Sundararaj & Prasad, ; Von Mecklenburg, ) activities, as well as in sustaining homeostatic functions (Jansen et al , ) favoured by the absence of a blood–brain barrier in the SV (Jansen & Flight, ).…”
Section: Introductionmentioning
confidence: 99%